Neutrophil Proteases Can Inactivate Human PAR3 and Abolish the Co-receptor Function of PAR3 on Murine Platelets - Cumashi, Albana; Ansuini, Helenia; Celli, Nicola; Blasi, Antonio De; O’Brien, Peter J.; Brass, Lawrence F.; Molino, Marina (Thrombosis and Haemostasis, 2001)
Three members of the protease-activated receptor family, PAR1, PAR3 and PAR4, are activated when thrombin cleaves the receptor N-terminus, exposing a tethered ligand. Proteases other than thrombin can also cleave PAR family members and, depending upon whether this exposes or removes the tethered ligand, either activate or disable the receptor. For example, on human platelets PAR1 is disabled by cathepsin G, although aggregation still occurs because cathepsin G can activate PAR4. The present studies examine the interaction of cathepsin G and a second neutrophil protease, elastase, with PAR3 using two model systems: COS-7 cells transfected with human PAR3 and mouse platelets, which express PAR3 and PAR4, but not PAR1. In contrast to human platelets, cathepsin G did not aggregate murine platelets, and prevented their activation only at low thrombin concentrations. Elastase had no effect on thrombin responses in mouse platelets, but when added to COS cells expressing human PAR3, both cathepsin G and elastase prevented activation of phospholipase C by thrombin. Notably, this inhibition occurred without loss of the binding sites for two monoclonal antibodies that flank the tethered ligand on human PAR3. We therefore conclude that 1) exposure to cathepsin G disables signaling through human PAR3, and prevents murine PAR3 from serving its normal role, which is to facilitate PAR4 cleavage at low thrombin concentrations, 2) elastase disables human, but not murine, PAR3, 3) in contrast to human PAR4, mouse PAR4 will not support platelet aggregation in response to cathepsin G, and 4) the inactivation of human PAR3 by cathepsin G and elastase involves a mechanism other than amputation of the tethered ligand domain. These results extend the range of possible interactions between PAR family members and proteases, and provide further support for species-specific differences in the interaction of these receptors with proteases other than thrombin.
Keywords: Proteases; protease-activated receptors; thrombin; cathepsin G